Oral Lymphoepithelial Cyst: A Collaborative Clinicopathologic Study of 132 Cases from Brazil - Cunha, John Lennon Silva (2021)
The oral lymphoepithelial cyst (OLC) is an uncommon lesion whose pathogenesis remains poorly understood. The aim of this study was to report the clinicopathologic features of the OLCs and to verify a possible association between OLCs and subgemmal neurogenous plaque (SNP) in the posterior lateral region of the tongue. A retrospective descriptive cross-sectional study was carried out. A total of 106,282 biopsy records of oral and maxillofacial lesions from six oral pathology services in Brazil were analyzed. All cases of OLCs were reviewed, and clinical and histopathological data were collected. Immunohistochemical reactions for S-100 protein were performed to confirm the diagnosis of SNP. Among all lesions, there were 132 (0.11%) cases of OLCs. The series comprised 83 females (62.9%) and 49 males (37.1%), with a 1.7:1 female-to-male ratio and a mean age of 45.8 ± 17.7 years. Most cases involved the tongue (n = 80; 62.0%) and presented clinically as asymptomatic papules or nodules with a yellow or whitish color. Microscopically, most of the cysts were entirely lined by parakeratinized stratified epithelium (n = 89; 67.4%) and filled with desquamated cells, keratin debris, amorphous eosinophilic material, and inflammatory cells in varying amounts. Connection with the epithelium of oral mucosa was observed in 18 cases (13.6%). SNP was found in 9/80 (11.2%) cases involving the tongue. The clinical and demographic features of OLCs were similar to those described in previous studies. Overall, this lesion has a predilection for the posterior region of the tongue of female adults. Clinicians must include the OLC in the differential diagnosis of yellow/white papules and nodules of the oral cavity.